Glial cell line-derived neurotrophic factor promotes increased phenotypic marker expression in femoral sensory and motor-derived Schwann cell cultures - Jesuraj, Nithya J. (2014)
Schwann cells (SCs) secrete growth factors and extracellular matrix molecules that promote neuronal survival and help guide axons during regeneration. Transplantation of SCs is a promising strategy for enhancing peripheral nerve regeneration. However, we and others have shown that after long-term in vitro expansion, SCs revert to a de-differentiated state similar to the phenotype observed after injury. In vivo, glial cell-line derived neurotrophic factor (GDNF) may guide the differentiation of SCs to remyelinate regenerating axons. Therefore, we hypothesized that exogenous GDNF may guide the differentiation of SCs into their native phenotypes in vitro through stimulation of GDNF family receptor (GFR)α-1. When activated in SCs, GFRα-1 promotes phosphorylation of Fyn, a Src family tyrosine kinase responsible for mediating downstream signaling for differentiation and proliferation. In this study, SCs harvested from the sensory and motor branches of rat femoral nerve were expanded in vitro and then cultured with 50 or 100 ng/mL of GDNF. The exogenous GDNF promoted differentiation of sensory and motor-derived SCs back to their native phenotypes, as demonstrated by decreased proliferation after 7 days and increased expression of S100Bβ and phenotype-specific markers. Furthermore, inhibiting Fyn with Src family kinase inhibitors, PP2 and SU6656, and siRNA-mediated knockdown of Fyn reduced GDNF-stimulated differentiation of sensory and motor-derived SCs. These results demonstrate that activating Fyn is necessary for GDNF-stimulated differentiation of femoral nerve-derived SCs into their native phenotypes in vitro. Therefore GDNF could be incorporated into SC-based therapies to promote differentiation of SCs into their native phenotype to improve functional nerve regeneration.